2011
DOI: 10.1007/s10562-011-0705-0
|View full text |Cite
|
Sign up to set email alerts
|

The First Case of Competitive Heterogeneously Catalyzed Hydrogenation using Continuous-Flow Fixed-Bed Reactor System: Hydrogenation of Binary Mixtures of Activated Ketones on Pt-Alumina and on Pt-Alumina-Cinchonidine Catalysts

Abstract: Under the experimental conditions of the Orito reaction the competitive hydrogenations of four binary mixtures of ethyl pyruvate (EP), methyl benzoylformate (MBF), pyruvic aldehyde dimethyl acetal (PA) and 2,2-diethoxyacetophenone (DAP) on unmodified Pt/Al 2 O 3 (racemic hydrogenation) and catalyst modified by cinchonidine (chiral hydrogenation) were studied using continuous-flow fixed-bed reactor system (CFBR). Conversions of chiral and racemic hydrogenations were determined under 4 MPa H 2 pressure, at 293 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Recently, silica supported catalysts have attracted the special attention of chemists [1][2][3] due to their eco-friendly nature, simple handling, recyclability, and high reactivity [4][5][6]. Similarly, protection of carbonyl functionaries from nucleophilic attack is one of the major problems faced during multistep syntheses.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, silica supported catalysts have attracted the special attention of chemists [1][2][3] due to their eco-friendly nature, simple handling, recyclability, and high reactivity [4][5][6]. Similarly, protection of carbonyl functionaries from nucleophilic attack is one of the major problems faced during multistep syntheses.…”
Section: Introductionmentioning
confidence: 99%
“…The inversions in the sense of the residual enantioselectivity confirmed previous conclusions related to the effects of the reaction parameters and substrate structure on the type and structure of the adsorbed intermediate complex. The influence of the substrate structure on this complex was demonstrated by racemic and asymmetric competitive hydrogenations of these activated ketones, initially in a batch system,25 and then in CF experiments 26. The CF system allowed rapid examinations of the competitive reactions through simple alternation of the individual hydrogenations and the reactions of their mixtures.…”
Section: Enantioselective Cf Hydrogenations Over Chirally Modified Camentioning
confidence: 99%
“…The CF system allowed rapid examinations of the competitive reactions through simple alternation of the individual hydrogenations and the reactions of their mixtures. The results of the competitive studies showed that both the enantioselectivities and rates of the asymmetric hydrogenations, that is, acceleration or deceleration compared with the racemic hydrogenations, are influenced by the structure of the substrate, as an indication that there are significant differences in certain surface reaction steps, which are affected by the strength and mode of adsorption of the substrates and modifiers 26…”
Section: Enantioselective Cf Hydrogenations Over Chirally Modified Camentioning
confidence: 99%
“…Design and preparation of solid phase supported catalysts have attracted a considerable attention. [1][2][3] Among solid supports used for catalysts preparation, catalysts which are include charcoal, 4 alumina, [5][6][7] and polymer, 8,9 silica affords some advantages such as good mechanical and thermal stabilities as well as ease of scalability. Many silica supported catalysts brings an aditional benefit decreasing a reactor corrosion and increase an environmentally safety.…”
Section: Introductionmentioning
confidence: 99%